Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Rusdian Rifa`i; Deni Pratidiana; Septiani Dwi Arifiyanti (JKPM (Jurnal Kajian Pendidikan Matematika), 2019)
This research aims to determine the presence or absence of improvement of student mathematical problem solving skills after applying the Problem Based Learning model. The method used in this research is the quasi-experimental method. Sampling was carried out with the Simple Random Sampling technique with a population of 66 students, and a sample used as many as 40 students from X A class as an experimental class and X B as the control class. Research instruments used in the form of a description test made based on the indicator of mathematical problem solving ability. Based on data analysis with ANOVA's one-lane testing method to test the proposed hypothesis, obtained results with value (Fcount = 19.283 > Ftabel = 4.10) At a rate of significance of 5%, then H0 rejected, so it can be concluded that there are Differences in the mathematical problem solving skills of students between classes taught with the Problem Based Learning model and conventional learning models.